Pengaruh Penerapan Model Pembelajaran PAIKEM GEMBROT terhadap Hasil Belajar Geografi pada Siswa Kelas XI IPS SMAN 1 Koto Baru Kabupaten Dharmasraya - Anatasya, Dewilla; Nova, Sari (Lembaga Yasin AlSys, 2023)
This research aims to determine the effect of implementing the PAIKEM GEMBROT learning model on improving student learning outcomes in geography subjects at SMA N 1 Koto Baru, Dharmasraya Regency. This type of research is quantitative, quasi-experimental method. The research design used was Pretest-Pottest Control Group Design. With the research sample, namely class XI IPS I as the experimental class and class XI IPS 2 as the control class. The sampling technique used purposive sampling with a sample size of 60 people. Based on the results of this research, the learning outcomes of the experimental class were higher than the control class. This can be seen from the average value of the experimental class of 86.78, while in the control class the result was 72.78. The t-test results were t count (6.807) < t table (1.672). So, H0 is accepted and Ha is rejected. This shows that there is an influence of the PAIKEM GEMBROT learning model on student learning outcomes in class XI IPS geography subjects at SMAN 1 Koto Baru Dharmasraya Regency.